ANALISIS PENGARUH LDR, NPL DAN OPERATIONAL EFFICIENCY RATIO TERHADAP RETURN ON ASSETS PADA BANK DEVISA DI INDONESIA PERIODE 2010-2012 - Hamidah, Hamidah; Siallagan, Goldan Merion; Mardiyati, Umi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
This research is performed on order to test analysis the influence of the Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) and Operational Efficiency Ratio (OER) toward Return On Asset (ROA) On Foreign Exchange Banks In Indonesia Period 2010-2012. Methodology research as the sample used purposive sampling, samplewas accured fromforeign banks in Indonesia. Data analysis with multi liniearregression of ordinary least square and hypotheses test used t-statistic and Fstatistic, a classic assumption examination to test the hypotheses.Based on normality test, multicolinearity test, heterosskedasticity test andautocorrelation test were not found variables that deviate from the classical assumptions, this indicatethat the available data has fulfill the condition to use multi linear regressionmodel. This result of research show that variable LDR and NPLpartially have positive influence but not significant toward ROA. Variable OERpartially have negative significant influencetoward ROA. Variable LDR, NPL and OER simultaneously have significant influence toward ROA. Keywords: Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Operational Efficiency Ratio (OER) and Return On Asset (ROA)